Dismantling the House that Albright Built: Dever’s Rise and Decline Narrative in the Reorientation of American Biblical Archaeology - Anderson, Malcolm (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
William G. Dever’s contribution to the reorientation of ‘biblical archaeology’ should not be under-estimated, although his historiography of the movement’s transition to ‘Syro-Palestinian archaeology’ certainly requires adjustment. In the paper, the significance of Dever’s 1972 Winslow Lectures, delivered at Seabury-Western Theological Seminary, is examined.